Keefektifan Program Adventure Based Counseling untuk Meningkatkan Kebahagiaan Mahasiswa - Setyowati, Aprilia; Suardiman, Siti Partini; Fauziah, Mufied (Jurnal Kajian Bimbingan dan Konseling, 2019)
A happy individual tends to produce positive things in life in terms of social self; study; and career aspects. This research is to find out the effectiveness of adventure based counseling (ABC) program to improve happiness in students. This research was conducted using experimental design with one group pretest-posttest model. The subject of this research was eleven students in the third semester of study program of guidance and counseling, Universitas Ahmad Dahlan (UAD) who were selected using purposive sampling technique. The pretest and posttest data was collected using a scale which was developed based on Seligman theory. The data was analyzed by non-parametric data analysis of Wilcoxon test. The results show that ABC program does not significantly influence happiness in students, but it gives influence to the aspect of meaningfulness and achievement.